Sankey diagrams for macroeconomics: A teaching complement bridging undergraduate and graduate Macro - de-Córdoba, Gonzalo F.; Molinari, Benedetto (Heliyon, 2022)
There is a widespread call in the academy to teach macroeconomics more homogeneously at the graduate and undergraduate levels. Current state-of-the-art research in macroeconomics obliges teachers of graduate courses to focus on dynamic stochastic general equilibrium (DSGE) models. At the same time, DSGE models have proven too complex for undergraduate-level macroeconomics, which is still grounded on classical model (e.g. IS-LM). In this paper, we propose a tool to bridge the gap between these two conceptual frameworks. Sankey diagrams for macroeconomics provide a coherent graphical analysis representing the aggregate economic activity either defined as in National Accounts, or in classical models, or as an equilibrium outcome of DSGE models. Thus, this tool can be used indifferently in graduate and undergraduate courses providing a guideline for students to recognize the same object of the analysis when jumping from undergraduate to graduate macro. Teaching macroeconomics; Sankey diagram; Undergraduate-level macroeconomics; DSGE models; Matplotlib Python.